Phylogenetics of two rhizomatous epiphytic species of Cymbidium (Orchidaceae; Cymbidieae): evidence from analyses of nuclear and plastid DNA - Xu, Shao-Wei; Gao, Xu-Yong; Zeng, Meng-Yao; Zhou, Cheng-Yuan; Liu, Zhong-Jian; Li, Ming-He (Phytotaxa, 2023)
The phylogenetic positions of two little-known species of Cymbidium (Cymbidiinae) with creeping rhizomatous habit, C. lii and C. repens, has previously been unclear. Here, we present a comprehensive molecular phylogenetic study of the genus based on nuclear ribosomal ITS and seven plastid regions. All analyses showed that C. lii and C. repens are sister to C. dayanum, an epiphytic species, with high support. However, many topological conflicts in inter- and intra-sectional relationships were observed in other parts of the trees, supporting existence of hybridization in Cymbidium but not affecting the taxa of interest in this study.